2011
DOI: 10.1038/npp.2011.212
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's Disease Therapeutics: New Developments and Challenges Since the Introduction of Levodopa

Abstract: The demonstration that dopamine loss is the key pathological feature of Parkinson's disease (PD), and the subsequent introduction of levodopa have revolutionalized the field of PD therapeutics. This review will discuss the significant progress that has been made in the development of new pharmacological and surgical tools to treat PD motor symptoms since this major breakthrough in the 1960s. However, we will also highlight some of the challenges the field of PD therapeutics has been struggling with during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
137
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(144 citation statements)
references
References 502 publications
(469 reference statements)
2
137
1
1
Order By: Relevance
“…59 Their wide distribution in the basal ganglia has generated interest to use them as a potential therapeutic target for treating PD and LID. 78 Lesion of the nigrostriatal pathway via MPTP treatment has been reported to increase mGlu5 receptor-specific binding, measured by autoradiography, in the striatum, 45,56,70 whereas other studies 55 and also the present one showed no significant increase in mGlu5 receptors in the striatum.…”
Section: Mglu2/3 Receptor Bindingcontrasting
confidence: 45%
“…59 Their wide distribution in the basal ganglia has generated interest to use them as a potential therapeutic target for treating PD and LID. 78 Lesion of the nigrostriatal pathway via MPTP treatment has been reported to increase mGlu5 receptor-specific binding, measured by autoradiography, in the striatum, 45,56,70 whereas other studies 55 and also the present one showed no significant increase in mGlu5 receptors in the striatum.…”
Section: Mglu2/3 Receptor Bindingcontrasting
confidence: 45%
“…There are several reported nonmotor side effects that can result from DBS therapy in PD patients (targeting either the STN or the GPi) including varying degrees of cognitive changes and changes in mood, 14 symptoms of mania or hypomania, 15 depression, 15 and even suicide. 3 Postoperative symptoms of psychosis have also been reported in PD patients receiving DBS treatment.…”
mentioning
confidence: 99%
“…The development of adenosine A2A selective antagonists, which have biological plausibility since these receptors occupy the striatum and colocalize with D2 and MGluR5 receptors, lead to great anticipation that these drugs would provide similar if not better efficacy than caffeine on a background of superior safety and tolerance. Preclinical studies of two such agents, istradefylline and preladenant, demonstrated antiparkinsonian effects and dyskinesia prevention [52][53][54][55]. However, istradefylline was the subject of four phase 3 trials in~1500 advanced PD patients and demonstrated only modest decrease in off times with an increase in dyskinesia.…”
Section: Pharmacogenomicsmentioning
confidence: 99%